NEW DATA ON CRETACEOUS VOLCANIC ARCS OF THE NORTHEASTERN ASIAN MARGIN - Chekhovich V.D.; Sukhov A.N.; Filatova N.I.; Vishnevskaya V.S.; Basov I.A. (My University, 2006)
Various models of evolution of the northwestern Pacific folded fringing during the Cretaceous were proposed in recent decades. Almost all of them consider the Late Cretaceous geodynamic evolution of the region as spatiotemporal succession of suprasubduction structures near the eastern margin of Asia that resulted from the subduction of the oceanic crust of the spreading Pacific.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая